Strand 1: The Unreliable Transcript, Contingent Technology and lnformal Practice in Asynchronous Learning Networks - Jones, Chris; Cawood, John (Proceedings of the International Conference on Networked Learning, 1998)
Some observers discern a paradigm shift in education in which the distinction between distance and campus learning is becoming blurred. The technology of computer conferencing has been merged with web technology in the form of the Asynchronous Learning Network. This paper examines the practices that develop when such new technologies and their associated learning strategics are deployed. It concentrates on a central feature of computer mediated conferencing, the transcript. This paper examines the claims made for transcripts as a basis for understanding just what goes on within the educational process. It concludes chat the transcript is generally an unreliable guide to the activity and process that takes place in a conference. In particular the transcript is shown to be unavailable to such techniques as content analysis and inappropriate to a simple conversational metaphor.